Integrasi Teknologi Informasi Dalam Penilaian Sumatif Tengah Semester Berbasis Digital: Implementasi Efektivitas Dan Tantangan Operasional - Murtanto, Tri Kuncoro Panji; Cahyani, Dewi; Ali, Moh (Universitas Pakuan, 2025)
INTEGRATION INFORMATION TECHNOLOGY IN DIGITAL-BASED MID-SEMESTER SUMMATIVE ASSESMENT: IMPLEMENTATION, EFFECTIVENESS AND OPERATIONAL CHALLENGESThis study aims to describe the form of information technology integration in the implementation of digital-based Mid-Semester Summative Assessment (PSTS) at SMK Negeri 1 Kandanghaur, Indramayu Regency, and evaluate its effectiveness in measuring student competencies and identifying implementation challenges. A qualitative approach with a case study was used, with data collection through in-depth interviews, direct observation, and document analysis of the PSTS Odd Semester of the 2025/2026 Academic Year. The results indicate that the school has adopted the Google Form platform for multiple-choice questions and the Exambro Android application as a test-taking medium. This system has proven effective in improving administrative efficiency, accelerating feedback, and maintaining exam integrity through an application lock feature that prevents access outside the platform. However, there are still findings that indicate that despite the adoption of technology, the assessment transformation has not yet touched the pedagogical essence, namely holistic, valid, and competency-based assessment. Research recommendations include the development of competency-based technical guidelines, ongoing training for teachers, and the provision of free internet access in schools to ensure the fairness and quality of assessments.